2015
DOI: 10.1073/pnas.1420370112
|View full text |Cite
|
Sign up to set email alerts
|

Immune-checkpoint proteins VISTA and PD-1 nonredundantly regulate murine T-cell responses

Abstract: V-domain immunoglobulin suppressor of T-cell activation (VISTA) is a negative immune-checkpoint protein that suppresses T-cell responses. To determine whether VISTA synergizes with another immune-checkpoint, programmed death 1 (PD-1), this study characterizes the immune responses in VISTA-deficient, PD-1-deficient (KO) mice and VISTA/PD-1 double KO mice. Chronic inflammation and spontaneous activation of T cells were observed in both single KO mice, demonstrating their nonredundancy. However, the VISTA/PD-1 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
259
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(274 citation statements)
references
References 36 publications
11
259
1
3
Order By: Relevance
“…43 It has been shown that VISTA and PD-1 exert non-redundant immune regulatory functions and synergistically regulate T-cell responses. 17 Combined blockade using monoclonal antibodies specific for VISTA and PD-L1 achieved optimal tumor-clearing therapeutic efficacy in murine tumor models. 14 Our data indicate an involvement of both VISTA and PD-1 pathways in the immune evasion in AML, therefore combinational treatment targeting these two inhibitory pathways may lead to a successful leukemia control and improve the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 It has been shown that VISTA and PD-1 exert non-redundant immune regulatory functions and synergistically regulate T-cell responses. 17 Combined blockade using monoclonal antibodies specific for VISTA and PD-L1 achieved optimal tumor-clearing therapeutic efficacy in murine tumor models. 14 Our data indicate an involvement of both VISTA and PD-1 pathways in the immune evasion in AML, therefore combinational treatment targeting these two inhibitory pathways may lead to a successful leukemia control and improve the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Combined inhibition of both VISTA and PD-1 pathways synergistically improves anti-tumor T cell activity. 14,17 These observations suggest a strong therapeutic potential of targeting VISTA for optimal tumor control. To investigate the effect of VISTA on anti-leukemia immune response in AML, we initiated a study using clinical samples collected from AML patients.…”
Section: Introductionmentioning
confidence: 98%
“…Anti-VISTA monoclonal antibody also intensified EAE. Synergies between VISTA and PD-1 in regulating T cell tolerance are demonstrated by studies of VISTA/PD-1 and VISTA/PD-L1 double knockout mice, which developed increased frequencies of activated T cells and inflammation compared to single knockout mice, but no spontaneous autoimmunity (152). These findings suggest that combined VISTA and PD-1 blockade may have therapeutic benefits associated with limited adverse events.…”
Section: V-domain Immunoglobulin-containing Suppressor Of T Cell Actimentioning
confidence: 94%
“…Frozen sections are sometimes used for these sensitive Abs (26), but this results in distorted tissue architecture and artifacts that compromise morphological studies. For these reasons, flow cytometry has long been the gold standard for analysis of immune infiltrates in the tumor microenvironment (27). However, flow cytometry does not provide sufficient contextual information, which was shown, in murine and human studies, to be important in understanding the biological basis of diseases and for predicting outcome in various types of cancer (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…pmel-1 TCR-transgenic mice were bred to Rag1 2/2 mice to generate pmel TCR/Rag1 2/2 mice. pmel TCR/Rag1 2/2 mice have CD8 + T cells expressing a transgenic TCR specific for mgp100 (25)(26)(27)(28)(29)(30)(31)(32)(33) peptide. TRP1 TCR/Rag1 2/2 -transgenic mice have CD4 + T cells expressing a transgenic TCR specific for mtyrp1 (113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127) peptide.…”
mentioning
confidence: 99%